Penerapan Model Pembelajaran Peer Teaching untuk Meningkatkan Keaktifan Siswa pada Mata Pelajaran Al-Qur’an Hadits Kelas XI-7 di MAN 1 Kota Bogor - Zahra, Ulvia; Gustiawati, Syarifah; Arif, Suyud (YASIN, 2025)
This study aims to determine the application of the Peer Teaching learning model in increasing student activity in the Al-Qur'an Hadith subject in class XI-7 MAN 1 Bogor City. The background of this study is based on the low student activity in learning the Al-Qur'an Hadith due to the use of conventional methods that do not actively involve students. This study uses a qualitative approach with a classroom action research (CAR) method consisting of two cycles. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that the application of the Peer Teaching model can significantly increase student activity, both in terms of asking questions, discussing, and expressing opinions during the learning process. Student activity increased from cycle I to cycle II after improvements were made to the implementation strategy. Thus, the Peer Teaching learning model has proven effective in creating a more interactive, collaborative and meaningful learning atmosphere in the Al-Qur'an Hadith subject.